Turning on anion and betaine hosting by a small structural change of a biomimetic cavity: a case study. Issue 7 (3rd July 2021) - De Leener, Gaël; Over, Diana; Reinaud, Olivia; Jabin, Ivan
ABSTRACT: This study explores the impact of a small structural modification on a biomimetic receptor. The hosting structure is a calix[6]arene capped by a tetraaza core. Two receptors are compared: one (1 ) presents three anisole units while the other (2 ) has three phenols. The latter was obtained with an excellent yield by selective demethylation thanks to a supramolecular strategy. Complexation studies showed that [2.H] + displays strong affinities for Cl −, NO3 −, HSO4 −, whereas [1.H] + is non-responsive. The anions are embedded at the level of the small rim, hydrogen-bonded to the protonated cap and the phenol groups. Ternary complexes are obtained in the presence of ammoniums. Finally, [2.H] + shows high affinity for small zwitterions presenting a carboxylate and an ammonium groups separated by one or two carbon atom(s), not three, due to multi-point recognition. These results open routes to the design of new receptors for a variety of anionic and zwitterionic guests. Abstract : uf0001